Diurnal cortisol rhythm: Associated with anxiety and depression, or just an indication of lack of energy?. Issue 2 (15th August 2015) - Harris, Anette; Endresen Reme, Silje; Tangen, Tone; Hansen, Åse Marie; Helene Garde, Anne; Eriksen, Hege Randi
Abstract: Dysregulation of hypothalamus–pituitary–adrenal-activity has been associated with low back pain (LBP). The underlying mechanisms are not fully explained, but psychological mechanisms are considered important. In this study we examine the association between psychiatric disorders/symptoms measured with different instruments, and cortisol in a population with LBP. Participants ( n =305) sick-listed 2–10 months due to non-specific LBP were included in the study. The screening instruments were the MINI-interview, HADS and HSCL-25. Saliva cortisol were measured on 2 consecutive days; at awakening, 30 min later, at 15:00 h and 22:00 h. Results showed no associations between any of the main diagnostic categories from the MINI-interview, or anxiety/depression measured with HADS or HSCL-25 and cortisol. However, significant associations were found between low cortisol awakening response, low cortisol slope during the day and the somatization scale from HSCL-25 (dizziness or lack of energy, lack of sexual interest, the feeling that everything requires substantial efforts, difficulties to fall asleep, headache). The results indicate that cortisol, may not be directly associated with psychopathology, such as anxiety and depression, but instead are associated with one dimension of the psychopathology, namely lack of energy. This could help explain the inconsistency in the literature, and it should be explored further. Highlights: The association among depression, anxiety and saliva cortisol was explored. Three instruments were used; MINI, HADS, HSCL-25. Cortisol was not associated with psychopathology, such as anxiety and depression. Cortisol associated with lack of energy, one dimension of the psychopathology.